KESADARAN KELUARGA PETANI TERHADAP PENTINGNYA PENDIDIKAN FORMAL - Syaefudin Syaefudin (UIN Sunan Kalijaga, 2018)
Abstract. This study aims to: First, find out how the community awareness of farm families in the village of Pogungrejo to formal education. Secondly, to know what factors influence the awareness of the farmer's family in Pogungrejo Village towards formal education. This type of research is qualitative. Using the sociological approach of education. Data collection is obtained directly from informants through interviews, observation, and documentation. Data analysis techniques used are with data reduction, data display, data verification and affirmation of conclusions. Result of analysis from this research; First, the awareness of Pogungrejo village farmers is in a state of naive consciousness. They tend to be static in terms of awareness for highly educated. Education is still viewed as a diploma printing machine for eligibility in job search. They have not understood the full meaning of life as a whole person. Secondly, the factors that influence the awareness of Pogungrejo Village Farmer's family towards the importance of formal education are: Economic factors, awareness factor on education, Parents attention factor, Environmental factors, Facility education facilities, Religious factors, Factors of urbanization temptation.